High-intensity training on CREB activation for improving brain health: a narrative review of possible molecular talks - Li, Ping; Hu, Yan; Tong, Ligang; Bi, Xuecui (Frontiers in Endocrinology, 2025)
Although physical exercise has obvious benefits in brain physiology, the molecular biomarkers induced by exercise protocols are inconclusive. Evidence indicates that exercise interventions are effective in shaping brain physiology. However, the potential mediator for improving brain functions is uncertain. CREB is one of the potential targets of exercise that triggers various molecular cross-talk to improve neurogenesis, long-term potentiation, and synaptogenesis. Therefore, CREB may be situated on the causal path between maintaining brain health and exercising. To support this, studies have shown that exercise-mediated CREB phosphorylation improves cognitive functions and memory. In addition, among the protocols of exercise (types, duration, and frequency), the intensity has been reported to be the most effective in triggering CREB-mediated molecular signaling. For example, HIT increases the synthesis of CREB, which may not only induce brain physiology but also induce brain pathology by higher activation of its downstream targets, such as BDNF. Therefore, this review aims to understand the effects of HIT on CREB function and how HIT can mediate the CREB-induced molecular cross-talk for maintaining brain health.